The effect of aquatic high-intensity interval training on aerobic performance, strength and body composition in a non-athletic population: systematic review and meta-analysis - Depiazzi, J.; Forbes, R.; Gibson, N.; Smith, N.; Wilson, A.; Boyd, Roslyn; Hill, Kylie (Sage Publications Ltd, 2018)
Objective: In a non-athletic population, to (1) investigate the effectiveness of high-intensity interval training in an aquatic environment (A-HIIT) on aerobic performance, strength, and body composition and (2) report on safety of this approach. Method: A systematic search was undertaken of six databases until May 2018. Trials were eligible for inclusion if they compared the effect of A-HIIT in a non-athletic population with a control group that received no exercise training. Data were extracted independently by two reviewers and meta-analyses were undertaken using a random effects model to produce standardized mean difference (SMD) and 95% confidence intervals (CIs). Risk of bias was assessed using Cochrane’s risk of bias tool. All studies were graded using Physiotherapy Evidence Database (PEDro) and Consensus for Exercise Reporting Template (CERT) scales to determine quality of reporting. Results: Eight studies reported over 13 papers met study criteria (n = 377). Compared with a control group, those who completed a program of A-HIIT demonstrated greater aerobic performance (SMD 0.69 (95% CI 0.39–0.98); I2 = 0%; n = 191) and lower limb muscle strength (SMD 0.30 (95% CI 0.04–0.56); I2 = 0%; n = 237). No differences were seen in measures of body composition or the number of adverse events. All studies were at risk of performance bias. The (mean ± SD) PEDro and CERT scores were 4.9 ± 1.5 and 15.1 ± 2.1, respectively. Conclusion: In a non-athletic population, A-HIIT was safe and may have improved aerobic performance and lower limb strength. The exercise interventions were well described and monitoring and reporting of exercise intensity in water was feasible.